2022
DOI: 10.5267/j.ijdns.2022.2.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of attitude to mediate the effect of trust, perceived behavior control, subjective norm and per-ceived quality on intention to reuse the COVID-19 website

Abstract: The objectives of this paper was to explain the effect of the variables trust, PBC, subjective norm, perceived quality, and re-usage intention on attitude and re-usage intention. This study's population consisted of Indonesians who visited the COVID-19 website to learn more about the progress of COVID-19. With the purposive sampling strategy, the sample size was as large as 238 participants. Path Analysis with the SEM-PLS approach was employed as the analytical technique. The findings revealed that trust, subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
3
1
0
4
Order By: Relevance
“…That changes in customer attitudes cannot change because important people around them agree, like, or recommend consuming organic rice. This research is in line with research conducted by (Farias et al, 2019;Yasa et al, 2022) which has similar results showing that subjective norms have an insignificant effect on attitude.…”
Section: The Influence Of Subjective Norms On Attitudesupporting
confidence: 92%
See 2 more Smart Citations
“…That changes in customer attitudes cannot change because important people around them agree, like, or recommend consuming organic rice. This research is in line with research conducted by (Farias et al, 2019;Yasa et al, 2022) which has similar results showing that subjective norms have an insignificant effect on attitude.…”
Section: The Influence Of Subjective Norms On Attitudesupporting
confidence: 92%
“…This can be seen that people around us agreeing with, or recommending organic rice products cannot influence buyers in repurchasing organic rice. This research is in line with research conducted by (Farias et al, 2019;Yasa et al, 2022) which has similar results showing that subjective norms have an insignificant effect on repurchasing intention through the mediating variable attitude.…”
Section: The Influence Of Subjective Norms On Repurchase Intention Th...supporting
confidence: 91%
See 1 more Smart Citation
“…These results are also supported by research by Chawla &Joshi (2019), andHanafizadeh et al,(2021), in which perceived usefulness has a significant influence on customer intentions to use mobile wallets. Results of other empirical studies (Yasa et al, 2022;Krishanan et al, 2016;Wida et al, 2016;Lai, 2016;Roh & Park, 2019;Sana et al, 2019;Aji & Dharmmesta, 2019;Ventre & Kolbe, 2020), found that perceived usefulness had a significant positive effect on intention to use, but in other studies (Santos et al, 2020;Troise et al, 2020;Purwanto & Mutahar, 2020;Nelwan et al, 2021), found that perceived usefulness has a positive but not significant effect on intention to use.…”
Section: Introductionmentioning
confidence: 91%
“…Menurut (Zeithaml, 1993;Berliana, 2022) Intention to Reuse merupakan ketertarikan individu untuk menggunakan Kembali (Ramadhani & Siregar, 2022). Intention to reuse merupakan perilaku pembeli supaya memakai Kembali barang maupun jasa (Yasa et al, 2022). Intention to reuse merupakan kondisi Dimana saat pembeli merasakan kepuasan maupun kebahagiaan ketika memakai suatu produk atau jasa yang ditawarkan (Indra, 2023).…”
Section: Customer Satisfactionunclassified